Non-Invasive Fiber Optic Probe Encapsulated Into PolyDiMethylSiloxane for Measuring Respiratory and Heart Rate of the Human Body - Jan Nedoma; Macel Fajkus; Petr Siska; Radek Martinek; Vladimir Vasinek (Advances in Electrical and Electronic Engineering, 2017)
This article describes the design and the functional verification of fiber optic system with an innovative non-invasive measuring probe for monitoring respiratory and heart rate. The measuring probe is based on Fiber Bragg Grating (FBG), and it is encapsulated in the PolyDiMethylSiloxane polymer (PDMS). PDMS offers a unique combination of suitable properties for the use in biomedical applications. The main advantages include inert to human skin and immunity to electromagnetic interference. The measuring probe is a part of contact strip which is placed on the chest of the patient. The measurement is based on sensing the movements of the thoracic cavity of the patient during breathing. Movement (mechanical stress) is transferred to FBG using the contact strip. Respiratory and heart rate are analyzed using the spectral evaluation of the measured signals. This monitoring method is fully dielectric; thus the absolute safety of the patient is ensured. The main contributions of the article are a design of non-invasive probe encapsulated into a PDMS polymer and implementation of the probe for humans using a contact strip. This combination forms an essential element of the measuring system. The set of experimental measurements verified functionality with respect to the position of the patient. Performed experiments proved the functionality of the presented solution so it can be utilized for further research in biomedical applications.